INDIGENOUS ECOLOGICAL KNOWLEDGE IN TRADITIONAL SILVICULTURAL PRACTICES OF INDONESIAN COMMUNITIES - Renawati, Pande Wayan; Williams, Sharon; Latu, Nia (Journal of Selvicoltura Asean, 2026)
Indigenous ecological knowledge (IEK) has long been integral to the traditional silvicultural practices of Indonesian communities. This knowledge, passed down through generations, plays a vital role in the sustainable management of forest resources. Despite its significance, the role of IEK in contemporary forest management practices remains underexplored in academic literature. This research aims to investigate the ways in which traditional silvicultural knowledge is applied in forest management by indigenous communities in Indonesia. The primary objective of this study is to examine the components and practices of traditional silviculture, focusing on how indigenous communities incorporate ecological knowledge into forest conservation and resource management. This research adopts a qualitative approach, using ethnographic fieldwork, interviews, and participant observation with indigenous forest communities in Indonesia. The study also involves the collection of relevant secondary data from local authorities and environmental organizations. The study finds that indigenous silvicultural practices are deeply rooted in ecological knowledge that promotes biodiversity conservation, enhances soil fertility, and ensures forest sustainability. These practices include selective logging, agroforestry systems, and forest regeneration methods that align with ecological principles. The integration of indigenous ecological knowledge into modern forest management practices is crucial for enhancing sustainability and addressing contemporary environmental challenges in Indonesia. The study calls for greater recognition and incorporation of these traditional practices in policy and management frameworks.